Parâmetros orbitais estelares homogêneos a partir de observações com grandes levantamentos espectroscópicos - Souza, Nayara Isabelle Feliciano (2025)
Large-scale spectroscopic surveys, such as APOGEE, GALAH, LAMOST, RAVE, SEGUE, and others, have revolutionized the way astrophysics has developed over the past twenty years. Combined with astrometric data from the Gaia mission and its radial velocity measurements provided by the Radial Velocity Spectrometer, these surveys have been exploring a wide range of Galactic regions, like the thin and thick disks, and the halo. This multi-faceted approach is imperative for building a comprehensive picture and state-of-the-art of the Milky Way. Beyond the spectroscopic and astrometric data, the derivation of orbital parameters for observed stars offers a crucial kinematic framework for unraveling the Galaxy’s formation and evolutionary history. In this context, the present work aims to construct the largest catalog of orbital parameters ever compiled to date, using the most up-to-date data from eight different spectroscopic surveys, combined with Gaia data and the AGAMA code for orbital modeling. The resulting catalog will include orbital parameters for more than 47 million stellar sources, among which more than 40 million are unique objects, along with probabilities of belonging to specific Galactic components based on kinematic classifications. We expect that this catalog will benefit a broad range of research areas, from stellar astrophysics and Galactic archaeology to exoplanetary science.